The Configuration of Work in the XXI Century: The Market Eloy Salmon and Molecular Movements of the Capital - María Luisa López Guerrero (Íconos)
The vendors of the street Eloy Salmon, located on the city La Paz, Bolivia, have been perceived as practicing an “informal” economy, excluded from the circuits of global capital accumulation and associated with poverty and low salaries. The history of these Bolivian vendors has been characterized by processes of exclusion and marginalization from the official economy and Bolivia’s state apparatus since its establishment in 1952. We propose – using the concept of David Harvey – that the vendors of Eloy Salmon are part of the molecular movements of the capital. This can be explained by observing that in their existing organization they have their own institutional forms, internal codes of exchange, and cultural practices that allow there to be social and local attachments, as well as the fostering of relationships with global capitalism, which creates “resistance” to the State.